Physicochemical and sensory analysis of drinking water from three districts of Tacna city, 2022 - Arratia Nina, Mauricio (2023)
A physicochemical analysis of the water from the Uchusuma river and a physicochemical and sensory analysis of the drinking water from different points of the city of Tacna, in the districts of Pocollay, Calana and Tacna, were carried out. The data obtained were comparatively analyzed with the ECA and LMP standards, the drinking water samples from the Pocollay, Calana and Tacna districts were also statistically analyzed to estimate the water quality. According to the physicochemical parameters of the samples from the Uchusuma River, it was possible to determine that the value is below or within the range. In the case of the physicochemical samples from the districts of Tacna and Calana, the DO values ​​exceed the LMP and the pH values ​​of Calana are outside the established range.